The Two Faces of Knowledge Search: New Solutions and Capability Development. Issue 12 (December 2013) - Tippmann, Esther; Mangematin, Vincent; Scott, Pamela Sharkey
Searching for knowledge to solve non-routine problems allows middle managers not only to design new solutions but also to develop organizational capabilities. We focus on knowledge search to develop our understanding of how individuals engage with organizational knowledge in practice, how they acquire and use knowledge, and the implications for organizational knowledge development. Investigating middle managers' knowledge search practices in response to non-routine events, we uncover four practices: isolating; overcoming knowledge distribution challenges; socializing; and mastering solution development. From these, we identify two aspects of knowledge search: not only can it produce new solutions but it can also have different effects in terms of developing organizational capabilities, either modifying existing routines or creating new ones. We argue that organizations with a knowledge use advantage, namely, an ability to mobilize accessible knowledge by organizing for knowledge circulation and a socialized search that deals with the organization's challenges of knowledge distribution in order to master solution development – especially at mid-level – can pursue capability development. We discuss the implications of our findings for the literature on organizational knowledge and middle managers' roles in organizational knowledge processes.